(3ebGdI GQTejOS aj JcSjQ GdOGFQIs
(3ChdgG (B:s
(3HYO GdOjHGLI cd OGFQI agj eSGhjI deKdK bGFe GdRGhjI jchf GMO VdYjI GdeMjWjf HGdRGhjI GdbGFeI eSGhjkG HGdfUa bWQ s
(3BNQgG (B:s
(3hGLJeYJ efgG GdbSj gj CVYGa hHbjJ bhS dRe Cf HYO Jdc GdbhS GdOhQI hHYO eLehY Jdc GdbSj ajchf bhS s
(3Vef eLehY , JQJjHgG (B: 7s
(3HgG fXGe GdJYbjHIs
(3hgj KdGK CTcGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs